Bilateral symmetrical maculopathy and heterochromia in Waardenburg syndrome - Paulo de Tarso Ponte Pierre-Filho; Lucas Linhares Pierre (Revista Brasileira de Oftalmologia, 2023)
ABSTRACT Waardenburg syndrome is a rare congenital genetic disorder characterized by sensorineural hearing loss and pigmentary abnormalities of the hair, skin, and eyes. Based on the different clinical presentations, it is divided into four subtypes as in WS1 to WS4. This report describes a 15-year-old boy who presented with low vision and bilateral hearing loss. His visual acuity was 20/200 in both eyes. Slit-lamp examination revealed complete iris heterochromia, with one blue iris and one brown iris. Fundus examination showed symmetrical pigmentation of the retina and choroid, with atrophy of the pigment epithelium in the macular region, notably also in the eye with normal iris pigment illustrating the broad spectrum of the iris and fundus pigmentation as part of this syndrome. A carefully clinical and ophthalmological evaluation should be done to differentiate various types of Waardenburg syndrome and other associated auditory-pigmentary syndrome. Early diagnosis in some cases may be crucial for the adequate development of patients affected with this condition.